A Low Cerebroplacental Ratio at 20-24 Weeks of Gestation Can Predict Reduced Fetal Size Later in Pregnancy or at Birth - Edgar Hernandez-Andrade (2018)
© 2017 © 2017 S. Karger AG, Basel. Copyright: All rights reserved. Aim: To determine whether Doppler evaluation at 20-24 weeks of gestation can predict reduced fetal size later in pregnancy or at birth. Methods: Fetal biometry and Doppler velocimetry were performed in 2,986 women with a singleton pregnancy at 20-24 weeks of gestation. Predictive performances of the umbilical artery pulsatility index (UA-PI) or the mean uterine artery pulsatility index (UtA-PI) >95th percentile, middle cerebral artery pulsatility index, or cerebroplacental ratio (CPR) <5th percentile for early small for gestational age (SGA; <34 weeks of gestation), late SGA (≥34 weeks of gestation), or SGA at birth (birthweight <10th percentile) were analyzed. Results: The prevalence of early SGA, late SGA, and SGA at birth was 1.1, 9.6, and 14.7%, respectively. A CPR <5th percentile had a positive likelihood ratio (LR+) of 8.2 (95% confidence interval [CI] 5.7-12.0) for early SGA, a LR+ of 1.6 (95% CI 1.1-1.2) for late SGA, and a LR+ of 1.9 (95% CI 1.4-2.6) for SGA at birth. A UtA-PI >95th percentile was associated with late SGA and SGA at birth, while an UA-PI >95th percentile was associated with early SGA. Associations were higher in fetuses with an estimated fetal weight <10th percentile. Conclusion: Fetal biometry and Doppler evaluation at 20-24 weeks of gestation can predict early and late SGA as well as SGA at birth.